Detecting Non Verbal and Vocal Expressions of Bullying in Kindergarten - Ntouka, Afrodite (International Journal of Criminology and Sociology, 2017)
The purpose of this paper is to examine the aggressiveness which is expressed by infants in kindergarten and is manifested as school bullying. More specifically, this paper is aiming in recording main bibliographic references of non verbal and vocal expression of preschoolers in anger situations and how those references are substantiated through surveys. Bibliography claims that school bullying does not occur unexpectedly, but instead there are apparent signs in behavior of preschoolers, that can be prevented before they occur. Throughout this paper however, what is in parallel aimed is the recording of the reasons that positively contribute to the expression of aggressive behavior in preschoolers. In this way, knowing the reason of causing an attitude, it could become easier and more efficient to prevent and efface that attitude. Many researchers conclude that parents and teachers have to cooperate and constantly communicate each other in order to significantly help preschoolers who, appear (show) aggressive behavior, to change its (their) behavior for the rest of their lives. Conclusions like that are under a new review in present study.